Second record of the Blacktip Grouper Epinephelus fasciatus (Teleostei: Serranidae) in the Mediterranean Sea - Gokoglu, Mehmet; Bicer, Erkan (Acta Aquatica: Aquatic Sciences Journal, 2022)
A red grouper was caught with a spear gun at depths of 8-10 m at the Alanya Harbor Breakwater. The purpose of this study is to determine this species, which is seen for the first time in the Mediterranean coasts of Turkey, and to add it to the Gulf of Antalya fish fauna. In the species identification, it was determined that this fish was Epinephelus fasciatus. E. fasciatus caught in Alanya Harbor is the second record for the Mediterranean and the first record for the Turkish coast. This fish became the second lessepsian Serranid species detected in the Gulf of Antalya, and the number of Serranid species with high economic value increased to nine with this species.